Sustainable approaches for algae utilisation in bioenergy production. (December 2018) - Chia, Shir Reen; Ong, Hwai Chyuan; Chew, Kit Wayne; Show, Pau Loke; Phang, Siew-Moi; Ling, Tau Chuan; Nagarajan, Dillirani; Lee, Duu-Jong; Chang, Jo-Shu
Abstract: Rapidly increasing global energy consumption has caused depletion of fossil fuels, leading to the search of alternative energy resources. One of the potential solutions is utilizing algae biomass as the source of bioenergy. To fulfil the high biomass demands for biofuel production, it is of pivotal importance to develop feasible technologies to enable economic, efficient and high density cultivation of algae. Algae can be cultivated in either open or closed systems in the presence of nutrients and light intensity. The maximum yield, growth rate and composition of algae can be optimized according to cultivation conditions, such as temperature, pH, light intensity and nutrient concentration. The potential types of algae in contributing carbohydrate and lipids to produce biofuel such as biodiesel, bioethanol and bio-gas are reviewed. Economic feasibilities of algae based fuel production are discussed based on Life Cycle Analysis. Current challenges and future prospective are also presented to realize the use of algae as a feedstock for commercial and cost effective fuel production.